First case report of Toxoplasma gondii-induced abortions and stillbirths in sheep in Argentina - Gual, Ignacio; Giannitti, Federico; Hecker, Yanina Paola; Shivers, J.; Entrocassi, Carolina; Morrell, Eleonora Lidia; Pardini, L.; Fiorentino, María Andrea; Rodríguez Fermepin, M.; Unzaga, Juan Manuel; Canton, German Jose; Venturini, María Cecilia; et al. (2018)
The aim of this study is to report an episode of reproductive losses due to toxoplasmosis in a sheep flock in Argentina. A total of 15 abortions and 9 stillbirths were recorded in a flock of 190 Texel ewes. The affected ewes were more likely to be seropositive for Toxoplasma gondii (15/24) than ewes that delivered normal lambs (5/34, OR =9.6, 95%CI =2.7–34.0, p =0.0004). A pair of aborted twins was recovered for diagnostic investigation. One of these fetuses and its dam were seropositive for T. gondii. Histological examination of the two fetuses revealed non-suppurative myocarditis and epicarditis, portal hepatitis and multifocal necrotizing encephalitis with protozoal cysts in the brain. T. gondii was detected intralesionally by immunohistochemistry in one fetus and by PCR in both. Further investigations are necessary to evaluate the economic losses due to T. gondii in the Argentinean ovine industry